Corrosion inhibitor, anticorrosive paint, laminate, method for manufacturing laminate, and method for preventing corrosion of substrate
A corrosion-resistant paint using plate-shaped alumina particles with specific properties addresses the need for improved corrosion protection in harsh environments by providing enhanced chemical stability and mechanical strength, effectively preventing rust and corrosion on steel structures.
Patent Information
- Application Number
- JP2020167274
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-09
- Filing Date
- 2020-10-01
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-10-01
AI Technical Summary
Existing anti-corrosion coatings for steel structures in harsh environments, such as coastal and underwater installations, require improved compositions for enhanced corrosion protection.
Development of a corrosion inhibitor containing plate-shaped alumina particles with specific properties, including a longitudinal relaxation time of 10 to 30 ppm and a high aspect ratio, which are incorporated into a corrosion-resistant paint to form a laminate, providing improved corrosion resistance.
The corrosion-resistant paint and laminate exhibit superior corrosion protection, with the alumina particles demonstrating high chemical stability, mechanical strength, and excellent adhesion to the substrate, effectively preventing rust, salt, and acid corrosion.
Smart Images

Figure 0007603409000001 
Figure 0007603409000002 
Figure 0007603409000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a corrosion inhibitor, an anticorrosive coating, a laminate, a method for producing a laminate, and a method for preventing corrosion of a substrate. This application claims priority to U.S. provisional application US62 / 912,652, filed October 9, 2019, the contents of which are incorporated herein by reference. [Background technology]
[0002] Steel structures such as ships, bridges, tanks, and plants are installed in coastal areas, river mouths, and underwater. These are often placed in extremely corrosive environments. For this reason, it is common to apply an anti-corrosion coating to the surfaces of these structures.
[0003] Such anticorrosive paints may contain particles. For example, Patent Document 1 discloses a heavy-duty anticorrosive composition containing 2 to 80% by weight of titanium or titanium alloy flakes in a resin. Patent Document 2 discloses an anticorrosive paint composition containing flaky potassium titanate particles in a resin composition. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 1-170670 [Patent Document 2] Japanese Patent Application Publication No. 6-329959 Summary of the Invention [Problem to be solved by the invention]
[0005] However, there continues to be a need for additional compositions to achieve corrosion protection benefits.
[0006] The present invention has been made in consideration of the above circumstances, and provides an anticorrosive agent and anticorrosive paint having anticorrosive effect, a laminate to which they are applied, a method for manufacturing a laminate, and a method for preventing corrosion of a substrate. [Means for solving the problem]
[0007] That is, the present invention includes the following aspects.
[0008] (1)Solid 27 A corrosion inhibitor containing plate-like alumina particles, in which the longitudinal relaxation time T1 for the peak of hexacoordinated aluminum at 10 to 30 ppm at a static magnetic field strength of 14.1 T is 5 seconds or longer in Al NMR analysis. (2) The corrosion inhibitor according to (1) above, wherein the platelet alumina particles contain silicon and / or germanium. (3) The corrosion inhibitor according to (2) above, wherein the platelet alumina particles contain mullite on the surface thereof. (4) The corrosion inhibitor according to any one of (1) to (3) above, wherein the plate-like alumina particles contain molybdenum. (5) The corrosion inhibitor according to (4) above, wherein the molybdenum content relative to 100% by mass of the plate-like alumina particles is 0.1 to 1% by mass, calculated as molybdenum trioxide. (6) An anticorrosive paint containing the anticorrosive agent according to any one of (1) to (5) above. (7) A laminate having a substrate and a layer containing the anticorrosive coating material described in (6) above. (8) The laminate according to (7) above, wherein the substrate is a metal. (9) A method for producing a laminate, comprising applying the anticorrosive coating material according to (6) above to a substrate. (10) A method for protecting a substrate from corrosion, comprising applying the anticorrosive coating material according to (6) above to the substrate. Effect of the Invention
[0009] According to the anticorrosive agent, anticorrosive paint, and laminate of the present invention, it is possible to provide an anticorrosive agent, anticorrosive paint, and laminate that can exhibit a good anticorrosive effect. Furthermore, according to the method for producing a laminate according to the present invention, a laminate capable of exhibiting a good corrosion prevention effect can be produced. Furthermore, according to the method for preventing corrosion of a substrate of the present invention, it is possible to impart a good anticorrosive effect to the substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, a corrosion inhibitor, an anticorrosive coating material, a laminate, a method for producing a laminate, and a method for preventing corrosion of a substrate according to one embodiment of the present invention will be described in detail.
[0011] <Corrosion inhibitor> The corrosion inhibitor according to one embodiment of the present invention (hereinafter, sometimes referred to as the "corrosion inhibitor of the embodiment" or simply as the "corrosion inhibitor") contains platelet alumina particles. The platelet alumina particles are solid. 27 In Al NMR analysis, the longitudinal relaxation time T1 for the peak of 6-coordinate aluminum at 10 to 30 ppm at a static magnetic field strength of 14.1 T is 5 seconds or more. The plate-like alumina particles have an aspect ratio of 5 to 500 and are solid. 27 In Al NMR analysis, the longitudinal relaxation time T1 for a peak of hexacoordinate aluminum at 10 to 30 ppm at a static magnetic field strength of 14.1 T is preferably 5 seconds or more.
[0012] The plate-like alumina particles contained in the corrosion inhibitor of the present embodiment have the above-mentioned composition and a dense crystal structure, and therefore have high chemical stability, so that the corrosion inhibitor of the present embodiment has excellent corrosion prevention effect. The anticorrosive effect of the anticorrosive agent can be confirmed by, for example, comparing the part where the anticorrosive agent is applied to the object to be coated with the part where the anticorrosive agent is not applied, and finding that the part where the anticorrosive agent is applied is more inhibited than the part where the anticorrosive agent is not applied. Corrosion includes metal corrosion (i.e. rust formation) and plastic corrosion (i.e. deterioration). The corrosion resistance, which indicates that the corrosion inhibitor exerts an anticorrosive effect, may be rust prevention, salt resistance or seawater resistance (inhibition of corrosion caused by salt), and may also be alkali resistance (inhibition of corrosion caused by alkali), acid resistance (inhibition of corrosion caused by acid), etc.
[0013] Next, the plate-like alumina particles contained in the corrosion inhibitor of this embodiment will be described in detail below.
[0014] [Plate-shaped alumina particles] The alumina particles of this embodiment have a plate-like shape and are solid. 27 In Al NMR analysis, the longitudinal relaxation time T1 is 5 seconds or more for a peak of hexacoordinated aluminum at 10 to 30 ppm at a static magnetic field strength of 14.1 T. The alumina particles of this embodiment are also referred to as "plate-like alumina particles," "plate-like alumina," or simply "alumina particles."
[0015] In this specification, "plate-like" refers to an aspect ratio of 2 or more, calculated by dividing the average particle diameter of the alumina particles by the thickness. In this specification, the "thickness of the alumina particles" refers to the arithmetic mean value of thicknesses measured for at least 50 plate-like alumina particles randomly selected from an image obtained by a scanning electron microscope (SEM). In addition, the "average particle diameter of the alumina particles" refers to the volume-based median diameter D from a volume-based cumulative particle size distribution measured by a laser diffraction particle size measurement device. 50 The value calculated as follows.
[0016] In the case of alumina particles, the following conditions of thickness, particle size, and aspect ratio can be combined in any way as long as the alumina particles are plate-like. The upper and lower limit values of the numerical ranges exemplified in these conditions can be freely combined.
[0017] The plate-like alumina particles preferably have a thickness of 0.01 μm or more and 5 μm or less, preferably 0.03 μm or more and 5 μm or less, more preferably 0.05 μm or more and 5 μm or less, more preferably 0.1 μm or more and 3 μm or less, and even more preferably 0.15 μm or more and 1.5 μm or less. Furthermore, when using large-diameter plate-like alumina particles, the thickness is preferably 3 μm or more, and more preferably 5 μm or more and 60 μm or less. Alumina particles having the above thickness are preferred because they have a high aspect ratio and excellent mechanical strength.
[0018] The plate-shaped alumina particles have an average particle diameter (D 50 ) is preferably 0.1 μm or more and 500 μm or less, more preferably 0.5 μm or more and 100 μm or less, and even more preferably 1 μm or more and 50 μm or less. When using larger plate-shaped alumina particles, the average particle diameter (D 50 ) is preferably 10 μm or more, more preferably 20 μm or more, even more preferably 22 μm or more, even more preferably 25 μm or more, and particularly preferably 31 μm or more. The upper limit of the average particle size is not particularly limited, but as an example, the average particle size (D 50 ) is preferably 10 μm or more and 500 μm or less, preferably 20 μm or more and 300 μm or less, more preferably 22 μm or more and 100 μm or less, even more preferably 25 μm or more and 100 μm or less, and particularly preferably 31 μm or more and 50 μm or less. The average particle size (D 50 Alumina particles having an average particle diameter (D ) of less than the upper limit value above exhibit a high corrosion prevention effect because the area of the upper or lower surface of the plate-like alumina plate is large. 50 ) are suitable for incorporation into anticorrosive paints.
[0019] The aspect ratio of the plate-like alumina particles, which is the ratio of the average particle diameter to the thickness, is preferably 2 to 500, more preferably 5 to 500, more preferably 10 to 500, more preferably 13 to 300, more preferably 15 to 300, and even more preferably 20 to 100. When the aspect ratio of the plate-like alumina particles is 2 or more, it is preferable because it can have two-dimensional blending characteristics, and when the aspect ratio of the plate-like alumina particles is 500 or less, it is preferable because it has excellent mechanical strength. When the aspect ratio is 15 or more, it is preferable because it exhibits a high anticorrosive effect. Furthermore, when large-diameter plate-like alumina particles are used, the aspect ratio, which is the ratio of the average particle diameter to the thickness, is preferably 2 or more and 50 or less, and more preferably 3 or more and 30 or less.
[0020] The plate-like alumina particles may be in the form of a circular plate or an elliptical plate, but the particle shape is preferably, for example, a polygonal plate from the viewpoint of ease of handling and production.
[0021] The plate-like alumina particles may be obtained based on any manufacturing method, but it is preferable to obtain them by firing an aluminum compound in the presence of a molybdenum compound (preferably further a potassium compound) and a shape control agent, in terms of a higher aspect ratio, better dispersibility, and better productivity. The shape control agent is preferably at least one selected from the group consisting of silicon, a silicon compound, and a germanium compound. Since the shape control agent is a source of Si for mullite described later, it is more preferable to use silicon or a silicon compound containing silicon element. In the above manufacturing method, the molybdenum compound is used as a fluxing agent. In the present specification, this manufacturing method using a molybdenum compound as a fluxing agent may be simply referred to as the "flux method". The flux method will be described in detail later. It is considered that, after the molybdenum compound reacts with the aluminum compound at high temperature by the firing to form aluminum molybdate, the aluminum molybdate is further decomposed into alumina and molybdenum oxide at a higher temperature, and the molybdenum compound is taken into the plate-like alumina particles. The molybdenum oxide is sublimated, recovered, and can be reused. In addition, when the plate-like alumina particles contain mullite in the surface layer, it is considered that the silicon or silicon atom-containing compound blended as a shape control agent reacts with the aluminum compound through molybdenum during this process, forming mullite in the surface layer of the plate-like alumina particles. More specifically, the mechanism of mullite formation is that on the alumina plate surface, the reaction of molybdenum with Si atoms forms Mo-O-Si, and the reaction of molybdenum with Al atoms forms Mo-O-Al, and high-temperature firing causes Mo to be released and mullite having Si-O-Al bonds is formed. Molybdenum oxide that is not incorporated into the plate-like alumina particles is preferably recovered and reused by sublimation. This reduces the amount of molybdenum oxide adhering to the plate-like alumina surface, and when the plate-like alumina particles are dispersed in a dispersion medium such as an organic binder like a resin or an inorganic binder like glass, the molybdenum oxide does not get mixed into the binder, making it possible to maximize the inherent properties of the plate-like alumina. In this specification, a material that has the property of being sublimable in the manufacturing method described below is called a fluxing agent, and a material that cannot be sublimated is called a shape control agent.
[0022] In the production of the plate-like alumina particles, by utilizing molybdenum and a shape control agent, the alumina particles have high crystallinity, a high alpha crystal rate, and are idiomorphic, thereby achieving excellent dispersibility, mechanical strength, and corrosion resistance.
[0023] When the plate-like alumina particles contain mullite in the surface layer, the amount of mullite generated in the surface layer of the plate-like alumina particles can be controlled by the proportions of the molybdenum compound and the shape control agent used, and in particular, by the proportion of silicon or a silicon compound containing silicon used as the shape control agent. The preferred amount of mullite generated in the surface layer of the plate-like alumina particles and the preferred proportions of the raw materials used will be described in detail later.
[0024] The plate-like alumina particles are plate-like alumina particles having an aspect ratio of 5 to 500 from the viewpoint of improving the corrosion prevention effect, and are solid. 27 In Al NMR analysis, the longitudinal relaxation time T1 for a peak of hexacoordinate aluminum at 10 to 30 ppm at a static magnetic field strength of 14.1 T is preferably 5 seconds or longer.
[0025] The longitudinal relaxation time T1 of 5 seconds or more means that the plate-like alumina particles have high crystallinity. It has been reported that the longer the longitudinal relaxation time in the solid state, the better the crystal symmetry and the higher the crystallinity (previously reported: Kitagawa Susumu et al., "Society of Coordination Chemistry Selection 4: Solution and Solid-State NMR of Multinuclear Species," Sankyo Publishing Co., Ltd., p. 80-82).
[0026] In the plate-like alumina particles, the longitudinal relaxation time T1 is preferably 5 seconds or more, more preferably 6 seconds or more, and even more preferably 7 seconds or more. In the plate-like alumina particles of the embodiment, the upper limit of the longitudinal relaxation time T1 is not particularly limited, but may be, for example, 22 seconds or less, 15 seconds or less, or 12 seconds or less. An example of the numerical range of the longitudinal relaxation time T1 exemplified above may be 5 seconds or more and 22 seconds or less, 6 seconds or more and 15 seconds or less, or 7 seconds or more and 12 seconds or less.
[0027] The plate-shaped alumina particles are solid 27It is preferable that no peak of 4-coordinate aluminum is detected at 60 to 90 ppm in Al NMR analysis at a static magnetic field strength of 14.1 T. Such plate-like alumina particles are considered to be less susceptible to breakage or falling off due to distortion of crystal symmetry caused by the inclusion of crystals with different coordination numbers, and tend to have better shape stability.
[0028] Conventionally, the degree of crystallinity of inorganic materials is generally evaluated by the results of XRD analysis and the like. However, the inventors have found that, by using the longitudinal relaxation time T1 as an index for evaluating the crystallinity of alumina particles, more accurate analysis results can be obtained than with conventional XRD analysis. The plate-like alumina particles according to the embodiment have a long longitudinal relaxation time T1 of 5 seconds or more, and the crystallinity of the alumina particles can be said to be high. That is, the plate-like alumina particles according to the embodiment are probably highly crystallinity-promoted, and therefore have improved chemical stability, strength, hardness, and the like, and are considered to have excellent corrosion prevention effects.
[0029] It has been difficult to obtain plate-shaped alumina particles with high crystallinity compared to spherical alumina particles. This is believed to be because, unlike spherical alumina particles, plate-shaped alumina particles require a bias in the direction of crystal growth during the production process. In contrast, the above-mentioned plate-like alumina particles that satisfy the above-mentioned longitudinal relaxation time T1 value are highly crystalline despite their plate-like shape, and therefore exhibit excellent chemical stability, as well as enhanced coating film stability and mechanical strength, making them extremely useful.
[0030] In addition, as an index of the plate-like shape, the plate-like alumina particles of the embodiment have a ratio I(006) / I(113) (hereinafter, I(006) / I(113) of the peak intensity I(006) corresponding to the (006) plane at 2θ=41.6±0.3 degrees and the peak intensity I(113) corresponding to the (113) plane obtained by X-ray diffraction measurement using Cu-Kα radiation, which is preferably 0.2 or more and 30 or less, more preferably 1 or more and 20 or less, even more preferably 3 or more and 10 or less, and particularly preferably 7.5 or more and 10 or less. In this case, the plate-like alumina particles may have, for example, an average particle diameter (D 50 ) is 10 μm or more and the thickness is 0.1 μm or more.
[0031] A large value of the (006 / 113) ratio means that the ratio of (006) planes to (113) planes is large, and is understood to mean that the plate-like alumina particles have significantly developed planes corresponding to the crystals with the (006) plane orientation. Such plate-like alumina particles have a large area of the developed upper or lower faces on the plate-shaped surface of the plate-like alumina, and the formation of the faces corresponding to the crystals with the (113) plane orientation is suppressed, so that they exhibit a high corrosion prevention effect even if the mass per particle is small.
[0032] The pH of the isoelectric point of the plate-like alumina particles is, for example, in the range of 2 to 6, preferably in the range of 2.5 to 5, and more preferably in the range of 3 to 4. The plate-like alumina particles having an isoelectric point within the above range have a high electrostatic repulsive force, and can enhance the dispersion stability when blended into the above-mentioned dispersion medium, and can be easily modified by surface treatment such as a coupling treatment agent for further improving performance.
[0033] The pH value of the isoelectric point is obtained by measuring the zeta potential with a zeta potential measuring device (Malvern Instruments, Zetasizer Nano ZSP) by stirring 20 mg of sample and 10 mL of 10 mM KCl aqueous solution for 3 minutes in stirring / degassing mode with a foam remover (Thinky Corporation, ARE-310), leaving it to stand for 5 minutes, and using the supernatant as the measurement sample. 0.1 N HCl is added to the sample with an automatic titration device, and the zeta potential is measured in the range up to pH = 2 (applied voltage 100 V, Monomodl mode), and the pH at the isoelectric point where the potential becomes zero is evaluated.
[0034] The plate-shaped alumina particles have a density of, for example, 3.70 g / cm 3 More than 4.10g / cm 3 and the density is 3.72 g / cm 3 More than 4.10g / cm 3 It is preferable that the density is 3.80 g / cm or less. 3 More than 4.10g / cm 3 It is more preferable that: The density can be measured using a Micromeritics dry automatic density meter, Accupic II1330, at a measurement temperature of 25°C and helium as the carrier gas, after pre-treating the plate-like alumina particles at 300°C for 3 hours.
[0035] For example, the specific surface area of the plate-shaped alumina particles is 0.01 m 2 / g or more 50m 2 / g or less, and 0.1m 2 / g or more 20m 2 / g or less is more preferable, and 0.5m 2 / g or more 10m 2 More preferably, it is 1.3m / g or less. 2 / g or more 10m 2 It is particularly preferable that the molecular weight is not more than 1 / g. The specific surface area can be determined as the surface area per 1 g of plate-like alumina particles measured by a nitrogen gas adsorption / desorption method using the BET method. The specific surface area can be measured by JIS Z 8830: BET one-point method (adsorption gas: nitrogen) or the like.
[0036] [alumina] The "alumina" contained in the plate-like alumina particles is aluminum oxide, and may be transition alumina of various crystal forms such as γ, δ, θ, κ, etc., or may contain alumina hydrate in the transition alumina, but is basically preferably the α crystal form (α type) in terms of superior mechanical strength or chemical stability. The α crystal form is a dense crystal structure of alumina, which enhances the mechanical strength or chemical stability of the plate-like alumina and is advantageous in improving the corrosion prevention effect. The α-crystallinity ratio is preferably as close to 100% as possible, since the inherent properties of the α-crystal form are more easily exhibited. The α-crystallinity ratio of the plate-like alumina particles is, for example, 90% or more, preferably 95% or more, and more preferably 99% or more.
[0037] [Silicon-Germanium] The platelet alumina particles of the embodiment may contain silicon and / or germanium. The silicon or germanium may be derived from silicon, a silicon compound, and / or a germanium compound that can be used as a shape control agent. By utilizing these, it is possible to easily produce plate-like alumina particles that satisfy the longitudinal relaxation time T1 value in the production method described below.
[0038] (silicon) The plate-like alumina particles according to the embodiment may contain silicon. The plate-like alumina particles according to the embodiment may contain silicon in a surface layer. Here, the "surface layer" refers to a region within 10 nm from the surface of the plate-like alumina particle according to the embodiment. This distance corresponds to the detection depth of the XPS used in the measurements in the examples.
[0039] The plate-like alumina particles may have silicon unevenly distributed in the surface layer. Here, "distributed unevenly in the surface layer" refers to a state in which the mass of silicon per unit volume in the surface layer is greater than the mass of silicon per unit volume in the rest of the surface layer. The fact that silicon is unevenly distributed in the surface layer can be determined by comparing the results of surface analysis by XPS and overall analysis by XRF.
[0040] The silicon contained in the plate-like alumina particles may be silicon alone or silicon in a silicon compound. The plate-like alumina particles may contain at least one selected from the group consisting of mullite, Si, SiO2, SiO, and aluminum silicate produced by reacting with alumina as silicon or a silicon compound, and may contain the above-mentioned substance in the surface layer. Mullite will be described later.
[0041] When silicon or a silicon compound containing silicon is used as a shape control agent, the plate-like alumina particles can detect Si by XRF analysis. The molar ratio of Si to Al [Si] / [Al] obtained by XRF analysis is, for example, 0.04 or less, preferably 0.035 or less, and more preferably 0.02 or less. Furthermore, the value of the molar ratio [Si] / [Al] is not particularly limited, but is, for example, 0.003 or more, preferably 0.004 or more, and more preferably 0.005 or more. The molar ratio of Si to Al, [Si] / [Al], of the plate-like alumina particles obtained by XRF analysis is, for example, 0.003 or more and 0.04 or less, preferably 0.004 or more and 0.035 or less, and more preferably 0.005 or more and 0.02 or less. The plate-like alumina particles having a molar ratio [Si] / [Al] within the above range obtained by the XRF analysis have a good plate-like shape. In addition, deposits are unlikely to adhere to the surface of the plate-like alumina particles, and the quality is excellent. The deposits are considered to be SiO2 particles, and are considered to be generated due to excess Si when the generation of mullite on the surface layer of the plate-like alumina particles becomes saturated. When using plate-like alumina particles having a larger particle size, the molar ratio of Si to Al, [Si] / [Al], obtained by XRF analysis, of the plate-like alumina particles is preferably 0.0003 or more and 0.01 or less, preferably 0.0005 or more and 0.0025 or less, and more preferably 0.0006 or more and 0.001 or less.
[0042] The plate-like alumina particles may contain silicon corresponding to the silicon or silicon compound containing silicon used in the production method thereof. The silicon content relative to 100 mass% of the plate-like alumina particles, calculated as silicon dioxide, is preferably 10 mass% or less, more preferably 0.001 to 5 mass%, further preferably 0.01 to 4 mass%, further preferably 0.3 to 2.5 mass%, and particularly preferably 0.6 to 2.5 mass%. When the silicon content is within the above range, the plate-like shape is well formed, and deposits that may be SiO2 particles are less likely to adhere to the surfaces of the plate-like alumina particles, resulting in excellent quality. When using plate-like alumina particles having a larger particle size, the silicon content relative to 100 mass% of the plate-like alumina particles, calculated as silicon dioxide, is preferably 10 mass% or less, more preferably 0.001 to 3 mass%, even more preferably 0.01 to 1 mass%, and particularly preferably 0.03 to 0.3 mass%. The silicon content can be determined by XRF analysis, which is carried out under the same conditions as those described in the examples below, or under compatible conditions that give the same measurement results.
[0043] (Mullite) The plate-like alumina particles of the embodiment may contain mullite. By containing mullite in the surface layer of the plate-like alumina particles, for example, when mixed with a resin to produce an anticorrosive coating, the anticorrosive coating has good compatibility with the resin, and the anchor effect increases adhesion, making it possible to provide an anticorrosive coating with even better anticorrosive effect. In addition, by containing mullite with low Mohs hardness in the surface layer of the plate-like alumina particles, it is possible to make the equipment for producing the anticorrosive coating less likely to wear. Mullite, when contained in the surface layer of the plate-like alumina particles, exerts a remarkable anti-corrosion effect and wear-reducing effect on the equipment. "Mullite," which may be contained in the surface layer of the plate-like alumina particles, is a composite oxide of Al and Si. X S Y O z However, there is no particular limit to the values of x, y, and z. A more preferable range is Al2Si1O5 to Al6Si2O 13 In the examples described later, the XRD peak intensity is confirmed for Al. 2.85 SiO 6.3 , Al3SiO 6.5 , Al 3.67 SiO 7.5 , Al4Si1O8, or Al6Si2O 13 The plate-shaped alumina particles contain Al 2.85 SiO 6.3 , Al3SiO 6.5 , Al 3.67 SiO 7.5 , Al4Si1O8, and Al6Si2O 13 The surface layer may contain at least one compound selected from the group consisting of: Here, the "surface layer" refers to within 10 nm from the surface of the plate-like alumina particle. This distance corresponds to the detection depth of XPS. This mullite surface layer is a very thin layer of 10 nm or less, and if there are many defects in the mullite crystals on the surface and interface, the compatibility with the resin will be further improved, and the corrosion prevention effect can be more significantly exhibited than mullite with no or few crystal defects. The plate-like alumina particles preferably have mullite unevenly distributed in the surface layer. Here, "distributed unevenly in the surface layer" refers to a state in which the mass of mullite per unit volume in the surface layer is greater than the mass of mullite per unit volume in the other parts of the surface layer. The uneven distribution of mullite in the surface layer can be determined by comparing the results of surface analysis by XPS and overall analysis by XRF. By distributing mullite unevenly in the surface layer, it is possible to exert excellent corrosion prevention effects and equipment wear reduction effects based on mullite at the same level with a smaller amount than when mullite is present not only in the surface layer but also in the other parts of the surface layer (inner layer).
[0044] In the plate-like alumina particles according to the embodiment, silicon or a silicon compound containing silicon is used as a shape control agent, and when the plate-like alumina particles according to the embodiment contain mullite in the surface layer, Si is detected by XPS analysis. When the plate-like alumina particles according to the embodiment contain mullite, the molar ratio [Si] / [Al] of Si to Al obtained in the XPS analysis is preferably 0.15 or more, more preferably 0.20 or more, and even more preferably 0.25 or more. According to the results of XPS, the value of [Si] / [Al] increases by increasing the amount of SiO2 charged as the raw material, but the value may plateau to a certain extent. This is considered to mean that the amount of Si on the plate-like alumina particles is saturated. Therefore, it is considered that the plate-like alumina particles having a molar ratio [Si] / [Al] of 0.20 or more, particularly 0.25 or more, are in a state in which the surface is coated with mullite. The above-mentioned coated state may mean that the entire surface of the plate-like alumina particles is coated with mullite, or at least a part of the surface of the plate-like alumina particles is coated with mullite. The upper limit of the molar ratio [Si] / [Al] in the XPS analysis is not particularly limited, but is preferably 0.4 or less, more preferably 0.35 or less, and even more preferably 0.3 or less. In the plate-like alumina particles according to the embodiment, the molar ratio of Si to Al, [Si] / [Al], obtained by XPS analysis, is preferably 0.15 or more and 0.4 or less, more preferably 0.20 or more and 0.35 or less, and even more preferably 0.25 or more and 0.3 or less. The plate-like alumina particles having a molar ratio [Si] / [Al] within the above range obtained by the XPS analysis have an appropriate amount of mullite contained in the surface layer, are excellent in quality, and have excellent corrosion prevention effects and equipment wear reduction effects. The XPS analysis is carried out under the same measurement conditions as those described in the Examples below, or under compatible conditions that give the same measurement results. In this embodiment, in the method for producing plate-like alumina described later, the charged silicon or silicon compound containing elemental silicon, such as SiO2, is converted to mullite with high efficiency, thereby obtaining plate-like alumina of excellent quality.
[0045] In the plate-like alumina particles according to the embodiment containing mullite, a diffraction peak derived from mullite is detected by XRD analysis. This diffraction peak derived from mullite can be clearly distinguished from the diffraction peak of silicon or a silicon compound containing silicon element, such as SiO2. In the plate-like alumina particles according to the embodiment, the ratio of the peak intensity of mullite observed at 2θ of 26.2±0.2° to the peak intensity of the (104) plane of α-alumina observed at 2θ of 35.1±0.2° obtained by XRD analysis may be, for example, 0.02 or more, 0.05 or more, or 0.1 or more. The upper limit of the peak intensity ratio is not particularly limited, but is, for example, 0.3 or less, preferably 0.2 or less, and more preferably less than 0.12. In the plate-like alumina particles according to the embodiment, the ratio of the peak intensity of mullite observed at 2θ of 26.2±0.2° to the peak intensity of the (104) plane of α-alumina observed at 2θ of 35.1±0.2°, as obtained by XRD analysis, may be, for example, 0.02 or more and 0.3 or less, 0.05 or more and 0.2 or less, or 0.1 or more and less than 0.12.
[0046] The presence or absence of mullite on the surface of the platelet alumina particles can be analyzed using a wide-angle X-ray diffraction (XRD) device such as Ultima IV manufactured by Rigaku Corporation. For example, a sample is placed on a measurement sample holder with a depth of 0.5 mm, and filled flat with a constant load. The sample is then set in the wide-angle X-ray diffraction (XRD) apparatus described above, and measurements are performed under the following conditions: Cu / Kα radiation, 40 kV / 40 mA, a scan speed of 2 degrees / min, and a scan range of 10 to 70 degrees. The presence or absence of mullite can be determined by the following formula, where the peak height of mullite observed at 2θ=26.2±0.2 degrees is A, the peak height of the (104) α-alumina plane observed at 2θ=35.1±0.2 degrees is B, and the baseline value at 2θ=30±0.2 degrees is C. The value of R may be, for example, 0.02 or more, 0.02 or more and 0.3 or less, 0.05 or more and 0.2 or less, or 0.1 or more and less than 0.12. R = (AC) / (BC) (R: Ratio of mullite peak height A to α-alumina (104) plane peak height B) The plate-like alumina particles having a peak intensity ratio value within the above range have an appropriate amount of mullite, are excellent in quality, and are more effective in preventing corrosion and reducing wear of equipment. The XRD analysis is carried out under the same measurement conditions as those described in the Examples below, or under compatible conditions that give the same measurement results.
[0047] In the platelet alumina particles according to the embodiment containing mullite, Si is detected by XRF analysis. The molar ratio [Si] / [Al] obtained by the XRF analysis may be one of the examples given above, and the plate-like alumina particles within the above range have an appropriate amount of mullite, are excellent in quality, and are more effective in preventing corrosion and reducing equipment wear. The plate-like alumina particles according to the embodiment contain silicon, which corresponds to the mullite based on silicon or silicon compound containing silicon used in the manufacturing method. The silicon content relative to 100 mass% of the plate-like alumina particles according to the embodiment may be the above-mentioned example, and it is preferable that the silicon content is within the above-mentioned range because the amount of mullite is appropriate. The silicon content can be determined by XRF analysis. The XRF analysis should be carried out under the same measurement conditions as those described in the Examples below, or under compatible conditions that give the same measurement results.
[0048] Moreover, the mullite of the surface layer may form a mullite layer, or may be in a state where mullite and alumina are mixed. The interface between the mullite and alumina of the surface layer may be in a state where the mullite and alumina are in physical contact with each other, or the mullite and alumina may form chemical bonds such as Si-O-Al. Compared to the combination of alumina and SiO2, the combination of alumina and mullite as essential components can bond alumina and mullite more firmly and make them less likely to peel off, from the viewpoint of the high similarity of the constituent atomic composition and the ease of forming chemical bonds such as Si-O-Al based on the flux method when the flux method is adopted. For this reason, if the amount of Si is at the same level, the combination of alumina and mullite as essential components is more preferable because it can exert the corrosion prevention effect and wear reduction effect of the equipment for a longer period of time. The technical effects of a combination containing alumina and mullite as essential components can be expected from either alumina and mullite alone or alumina, mullite and silica, but if anything, the combination of the former two will provide a higher level of technical effect.
[0049] (germanium) The plate-like alumina particles of the embodiment may contain germanium. Also, the plate-like alumina particles may contain germanium in the surface layer. By containing germanium or a germanium compound in the plate-like alumina particles, for example, when mixed with a resin to produce an anticorrosive paint, the plate-like alumina particles have good compatibility with the resin, and the adhesion is increased by the anchor effect, so that an anticorrosive paint with even better anticorrosive effect can be provided. Also, by containing germanium or a germanium compound with low Mohs hardness in the surface layer of the plate-like alumina particles, the equipment for producing the anticorrosive paint can be made less likely to be worn. Although it depends on the raw material used, the plate-shaped alumina particles are germanium or germanium compounds such as Ge, GeO2, GeO, GeCl2, GeBr4, GeI4, GeS2, AlGe, GeTe, GeTe 3、It may contain at least one selected from the group consisting of compounds such as As2, GeSe, GeS3As, SiGe, Li2Ge, FeGe, SrGe, GaGe, and oxides thereof, and the above substance may be contained in the surface layer. In addition, the "germanium or germanium compound" contained in the plate-like alumina particles and the "raw germanium compound" used as the shape control agent of the raw material may be the same type of germanium compound. For example, GeO2 may be detected in the plate-like alumina particles produced by adding GeO2 to the raw material.
[0050] Germanium or a germanium compound is contained in the surface layer of the plate-like alumina particles, and thereby exerts a remarkable anti-corrosion effect and an effect of reducing wear of equipment. Here, the "surface layer" refers to the area within 10 nm from the surface of the plate-like alumina particles. The plate-like alumina particles preferably have germanium or germanium compounds unevenly distributed in the surface layer. Here, "distributed unevenly in the surface layer" refers to a state in which the mass of germanium or germanium compounds per unit volume in the surface layer is greater than the mass of germanium or germanium compounds per unit volume in the other layers. The uneven distribution of germanium or germanium compounds in the surface layer can be determined by comparing the results of surface analysis by XPS and overall analysis by XRF. By distributing germanium or germanium compounds unevenly in the surface layer, the germanium or germanium compounds can exhibit the anticorrosive effect and wear reduction effect of equipment based on germanium or germanium compounds at a similar level with a smaller amount than when germanium or germanium compounds are present not only in the surface layer but also in the other layers (inner layer).
[0051] Germanium or a germanium compound is contained in the surface layer of the plate-like alumina particles, and thus exhibits a remarkable anticorrosive effect and wear-reducing effect on equipment. Here, the "surface layer" refers to within 10 nm from the surface of the plate-like alumina particles according to the embodiment. The surface layer containing germanium is a very thin layer of within 10 nm, and in the case of germanium dioxide, for example, if the germanium dioxide structure on the surface and interface has many defects, it will have better compatibility with resin, and will exhibit a more remarkable anticorrosive effect and wear-reducing effect on equipment compared to germanium dioxide with no or few structural defects. In the plate-like alumina particles according to the embodiment, germanium or germanium compounds are preferably distributed unevenly in the surface layer. Here, "distributed unevenly in the surface layer" refers to a state in which the mass of germanium or germanium compounds per unit volume in the surface layer is greater than the mass of germanium or germanium compounds per unit volume in the other layers. The distribution of germanium or germanium compounds unevenly in the surface layer can be determined by comparing the results of surface analysis by XPS and overall analysis by XRF. By distributing germanium or germanium compounds unevenly in the surface layer, the germanium or germanium compounds can be used in smaller amounts and at the same level as when germanium or germanium compounds are present not only in the surface layer but also in the other layers (inner layer).
[0052] The plate-like alumina particles according to the embodiment contain germanium or a germanium compound in the surface layer, so that Ge is detected by XPS analysis. The plate-like alumina particles according to the embodiment have a molar ratio of Ge to Al [Ge] / [Al] obtained by XPS analysis of preferably 0.005 or more, more preferably 0.01 or more, even more preferably 0.02 or more, and particularly preferably 0.03 or more. By increasing the amount of GeO2 charged as the raw material, the value of [Ge] / [Al] increases, but the value may plateau to a certain extent. This is considered to mean that the amount of Ge on the plate-like alumina particles has reached saturation. The entire surface of the plate-like alumina particles may be coated with germanium or a germanium compound, or at least a part of the surface of the plate-like alumina particles may be coated with germanium or a germanium compound. The upper limit of the molar ratio [Ge] / [Al] in the XPS analysis is not particularly limited, but may be 0.3 or less, 0.25 or less, 0.2 or less, 0.17 or less, or 0.1 or less. The plate-like alumina particles according to the embodiment may have a molar ratio of Ge to Al, [Ge] / [Al], obtained by XPS analysis, of 0.005 or more and 0.3 or less, 0.005 or more and 0.25 or less, 0.01 or more and 0.2 or less, 0.02 or more and 0.17 or less, or 0.03 or more and 0.1 or less. The plate-like alumina particles having a molar ratio [Ge] / [Al] within the above range obtained by the XPS analysis have an appropriate amount of germanium or germanium compound contained in the surface layer, are well formed in a plate-like shape, are of excellent quality, and have excellent corrosion prevention effects and equipment wear reduction effects. The XPS analysis is carried out under the same measurement conditions as those described in the Examples below, or under compatible conditions that give the same measurement results. In this embodiment, in the method for producing plate-like alumina described below, a raw material germanium compound such as GeO2 charged as a shape control agent is highly efficiently formed as a layer containing germanium on the surface of the plate-like alumina, thereby obtaining plate-like alumina of excellent quality.
[0053] In the plate-like alumina particles according to the embodiment, when a germanium compound is used as a shape control agent, Ge can be detected by XRF analysis. In the plate-like alumina particles according to the embodiment, the molar ratio [Ge] / [Al] of Ge to Al obtained by XRF analysis is, for example, 0.08 or less, preferably 0.05 or less, and more preferably 0.03 or less. Furthermore, the value of the molar ratio [Ge] / [Al] is not particularly limited, but is, for example, 0.0005 or more, preferably 0.001 or more, and more preferably 0.0015 or more. The plate-like alumina particles according to the embodiment have a molar ratio of Ge to Al, [Ge] / [Al], obtained by XRF analysis, of, for example, 0.0005 or more and 0.08 or less, preferably 0.003)1 or more and 0.05 or less, and more preferably 0.0015 or more and 0.03 or less. The plate-like alumina particles having a molar ratio [Ge] / [Al] value obtained by the XRF analysis within the above range contain an appropriate amount of germanium or germanium compound, have a well-formed plate-like shape, are of excellent quality, and have excellent corrosion prevention effects and equipment wear reduction effects.
[0054] The plate-like alumina particles contain germanium corresponding to the raw germanium compound used in the production method. The germanium content relative to 100% by mass of the plate-like alumina particles is preferably 10% by mass or less, more preferably 0.001-5% by mass, even more preferably 0.01-4% by mass, and particularly preferably 0.1-3.0% by mass, calculated as germanium dioxide. If the germanium content is within the above range, the amount of germanium or germanium compound is appropriate, and a plate-like shape is favorably formed, which is preferable. The germanium content can be determined by XRF analysis. The XRF analysis should be carried out under the same measurement conditions as those described in the Examples below, or under compatible conditions that give the same measurement results.
[0055] The germanium or germanium compound of the surface layer may form a layer, or may be in a state where germanium or germanium compound and alumina are mixed. The interface between the germanium or germanium compound of the surface layer and alumina may be in a state where the germanium or germanium compound and alumina are in physical contact with each other, or the germanium or germanium compound and alumina may form a chemical bond such as Ge-O-Al.
[0056] [molybdenum] The plate-like alumina particles of the embodiment may contain molybdenum. In addition, the plate-like alumina particles preferably contain molybdenum in their surface layers. The molybdenum may be derived from a molybdenum compound used as a fluxing agent in the method for producing alumina particles described below.
[0057] Molybdenum has catalytic and optical properties, and by using molybdenum, it is possible to produce plate-like alumina particles that are highly crystalline despite their plate-like shape and have excellent corrosion prevention properties, in a production method described below.
[0058] By increasing the amount of molybdenum used, the particle size and the above (006 / 113) ratio values are satisfied, and the corrosion prevention effect of the obtained alumina particles tends to be further improved. Furthermore, by utilizing molybdenum, the formation of mullite is promoted, and plate-like alumina particles having a high aspect ratio and excellent corrosion prevention effect can be produced.
[0059] The molybdenum is not particularly limited, but includes molybdenum metal, molybdenum oxide, partially reduced molybdenum compounds, molybdates, and the like. The molybdenum compound may be contained in the platelet alumina particles in any of its possible polymorphic forms or in combination, and may be contained in the platelet alumina particles as α-MoO 3 , β-MoO 3 , MoO 2 , MoO, molybdenum cluster structures, and the like.
[0060] The form in which molybdenum is contained is not particularly limited, and may be contained in a form in which it is adhered to the surface of the plate-like alumina particles, or may be contained in a form in which it is substituted for part of the aluminum in the crystal structure of the alumina, or may be a combination of these.
[0061] The molybdenum content relative to 100 mass% of the plate-like alumina particles obtained by XRF analysis is preferably 10 mass% or less in terms of molybdenum trioxide, and by adjusting the firing temperature, firing time, and sublimation rate of the molybdenum compound, it is more preferably 0.001 to 5 mass%, further preferably 0.01 to 5 mass%, further preferably 0.1 to 1.5 mass%, and particularly preferably 0.1 to 1 mass%. A molybdenum content of 10 mass% or less is preferable because it improves the α single crystal quality of the alumina. When using plate-like alumina particles having a larger particle size, the molybdenum content relative to 100 mass% of the plate-like alumina particles according to the embodiment is preferably 10 mass% or less, calculated as molybdenum trioxide, and by adjusting the firing temperature, firing time, and sublimation rate of the molybdenum compound, the molybdenum content is more preferably 0.1 to 5 mass%, and even more preferably 0.3 to 1 mass%. The molybdenum content can be determined by XRF analysis, which should be carried out under the same conditions as those described in the examples below, or under compatible conditions that give the same measurement results.
[0062] The amount of Mo on the surface of the alumina particles can be analyzed using the above-mentioned X-ray photoelectron spectroscopy (XPS) device.
[0063] [potassium] The plate-like alumina particles may further contain potassium.
[0064] The potassium may be derived from potassium that can be used as a fluxing agent in the method for producing alumina particles described below. By utilizing potassium, the particle size of the alumina particles can be appropriately increased in the method for producing alumina particles described below.
[0065] The potassium is not particularly limited, but includes potassium metal, potassium oxide, partially reduced potassium compounds, and the like.
[0066] The form in which potassium is contained is not particularly limited, and may be contained in a form in which potassium is attached to the surface of the tabular alumina of the tabular alumina particles, or may be contained in a form in which potassium is substituted for part of the aluminum in the crystal structure of the alumina, or may be a combination of these.
[0067] The potassium content relative to 100% by mass of the alumina particles, as calculated by XRF analysis, is preferably 0.01% by mass or more, more preferably 0.01 to 1.0% by mass, even more preferably 0.03 to 0.5% by mass, and particularly preferably 0.05 to 0.3% by mass. Alumina particles having a potassium content within the above range are preferred because they have a plate-like shape and have suitable values such as an average particle size.
[0068] (other atoms) The other atoms refer to those that are intentionally added to the alumina particles for the purpose of imparting mechanical strength or electrical or magnetic functions, within the scope of not impairing the effects of the present invention.
[0069] The other atoms are not particularly limited, but include zinc, manganese, calcium, strontium, yttrium, etc. These other atoms may be used alone or in combination of two or more.
[0070] The content of other atoms in the alumina particles is preferably 5 mass % or less, and more preferably 2 mass % or less, based on the mass of the alumina particles.
[0071] [Inevitable impurities] The alumina particles may contain unavoidable impurities.
[0072] Inevitable impurities are impurities that originate from metal compounds used in production, are present in raw materials, or are inevitably mixed into alumina particles during the production process. Although they are not actually required, they are present in trace amounts and do not affect the properties of the alumina particles.
[0073] The inevitable impurities are not particularly limited, but include magnesium, calcium, strontium, barium, scandium, yttrium, lanthanum, cerium, sodium, etc. These inevitable impurities may be contained alone or in combination of two or more kinds.
[0074] The content of unavoidable impurities in the alumina particles is preferably 10,000 ppm or less, more preferably 1,000 ppm or less, and further preferably 10 to 500 ppm, based on the mass of the alumina particles.
[0075] [Organic compounds] In one embodiment, the plate-like alumina particles may contain an organic compound. The organic compound is present on the surface of the plate-like alumina particles and has a function of adjusting the surface properties of the plate-like alumina particles. For example, the plate-like alumina particles having an organic compound on the surface have improved affinity with resins, and therefore can maximize the function of the plate-like alumina particles as a corrosion inhibitor.
[0076] Organic compounds include, but are not limited to, organosilanes, alkylphosphonic acids, and polymers.
[0077] Examples of the organic silane include alkyltrimethoxysilanes or alkyltrichlorosilanes having an alkyl group having 1 to 22 carbon atoms, such as methyltrimethoxysilane, dimethyldimethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, isopropyltrimethoxysilane, isopropyltriethoxysilane, pentyltrimethoxysilane, and hexyltrimethoxysilane; 3,3,3-trifluoropropyltrimethoxysilane, tridecafluoro-1,1,2,2-tetrahydrooctyl)trichlorosilanes; phenyltrimethoxysilane, phenyltriethoxysilane, p-chloromethylphenyltrimethoxysilane, and p-chloromethylphenyltriethoxysilanes.
[0078] Examples of the phosphonic acid include methylphosphonic acid, ethylphosphonic acid, propylphosphonic acid, butylphosphonic acid, pentylphosphonic acid, hexylphosphonic acid, heptylphosphonic acid, octylphosphonic acid, decylphosphonic acid, dodecylphosphonic acid, octadecylphosphonic acid, 2-ethylhexylphosphonic acid, cyclohexylmethylphosphonic acid, cyclohexylethylphosphonic acid, benzylphosphonic acid, phenylphosphonic acid, and dodecylbenzenephosphonic acid.
[0079] As the polymer, for example, poly(meth)acrylates can be suitably used.Specific examples include polymethyl(meth)acrylate, polyethyl(meth)acrylate, polybutyl(meth)acrylate, polybenzyl(meth)acrylate, polycyclohexyl(meth)acrylate, polyt-butyl(meth)acrylate, polyglycidyl(meth)acrylate, polypentafluoropropyl(meth)acrylate, etc., and also include general-purpose polymers such as polystyrene, polyvinyl chloride, polyvinyl acetate, epoxy resin, polyester, polyimide, polycarbonate, etc.
[0080] The organic compound may be contained alone or in combination of two or more kinds.
[0081] The form in which the organic compound is contained is not particularly limited, and the organic compound may be bonded to the alumina via a covalent bond, or may coat the alumina.
[0082] The content of the organic compound is preferably 20% by mass or less, more preferably 10% by mass or more and 0.01% by mass or less, based on the mass of the alumina particles. When the content of the organic compound is 20% by mass or less, it is preferable because the physical properties derived from the plate-like alumina particles can be easily expressed.
[0083] <Method of manufacturing plate-like alumina particles> The method for producing the plate-like alumina particles is not particularly limited, and known techniques can be appropriately applied. From the viewpoint of being able to suitably control alumina having a high α crystallization rate at a relatively low temperature, a production method using a flux method utilizing a molybdenum compound is preferably applied.
[0084] More specifically, a preferred method for producing plate-like alumina particles includes a step of calcining an aluminum compound in the presence of a molybdenum compound and a shape control agent (calcination step). The calcination step may be a step of calcining a mixture obtained in a step of obtaining a mixture to be calcined (mixing step).
[0085] [Mixing process] The mixing step is a step of mixing an aluminum compound, a molybdenum compound, and a shape control agent to obtain a mixture. The mixture preferably further contains a potassium compound. The contents of the mixture will be described below.
[0086] (Aluminum Compounds) The aluminum compound is a raw material for the plate-like alumina particles of this embodiment, and is not particularly limited as long as it becomes alumina by heat treatment. For example, aluminum chloride, aluminum sulfate, basic aluminum acetate, aluminum hydroxide, boehmite, pseudo-boehmite, transition alumina (γ-alumina, δ-alumina, θ-alumina, etc.), α-alumina, mixed alumina having two or more crystal phases, etc. can be used, and the physical form, such as the shape, particle size, and specific surface area, of these aluminum compounds as precursors is not particularly limited.
[0087] According to the flux method described in detail below, the aluminum compound can be suitably used regardless of its shape, for example, spherical, amorphous, oriented structure (wire, fiber, ribbon, tube, etc.), sheet, etc.
[0088] Similarly, the particle size of the aluminum compound may be from several nm to several hundred μm in the case of the flux method described in detail below.
[0089] The specific surface area of the aluminum compound is not particularly limited. Since the molybdenum compound acts effectively, the larger the specific surface area, the more preferable it is. However, by adjusting the firing conditions and the amount of the molybdenum compound used, any specific surface area can be used as the raw material.
[0090] The aluminum compound may be composed of only the aluminum compound, or may be a complex of the aluminum compound and an organic compound. For example, an organic / inorganic complex obtained by modifying an aluminum compound with an organic silane, an aluminum compound complex adsorbing a polymer, etc. may be suitably used. When using these complexes, the content of the organic compound is not particularly limited, but from the viewpoint of efficiently producing plate-like alumina particles, the content is preferably 60% by mass or less, more preferably 30% by mass or less.
[0091] (shape control agent) To form the plate-like alumina particles according to the embodiment, a shape control agent can be used, which plays an important role in the growth of plate-like crystals of alumina by calcining an alumina compound in the presence of a molybdenum compound.
[0092] The state in which the shape control agent is present is not particularly limited, and for example, a physical mixture of the shape control agent and the aluminum compound, or a complex in which the shape control agent is present uniformly or locally on the surface or inside of the aluminum compound, etc. can be suitably used.
[0093] The shape control agent may be added to the aluminum compound, or may be contained in the aluminum compound as an impurity.
[0094] The shape control agent plays an important role in the growth of plate-like crystals. In the molybdenum oxide flux method, molybdenum oxide reacts with an aluminum compound to form aluminum molybdate, and then the change in chemical potential during the decomposition of this aluminum molybdate serves as the driving force for crystallization, forming hexagonal bipyramidal polyhedral particles with well-developed idiomorphic faces (113). In the manufacturing method of the embodiment, the shape control agent is localized near the particle surface during the α-alumina growth process, significantly inhibiting the growth of the idiomorphic faces (113), which results in relatively fast growth of the crystal orientation in the face direction, and the (001) or (006) face grows, forming a plate-like shape. By using a molybdenum compound as a flux agent, it is possible to more easily form molybdenum-containing plate-like alumina particles with a high α-crystallization rate.
[0095] It should be noted that the above mechanism is merely speculative, and even if the effects of the present invention are obtained through a mechanism different from the above mechanism, this is still within the technical scope of the present invention.
[0096] As for the type of shape control agent, it is preferable to use at least one selected from the group consisting of silicon, silicon compounds, and germanium compounds, from the viewpoint of being able to produce plate-like alumina particles with a higher aspect ratio, better dispersibility, and better productivity. Silicon or silicon compounds and germanium compounds can be used in combination. From the viewpoint of being a source of Si for mullite and being able to efficiently produce mullite, it is preferable to use silicon or silicon compounds containing silicon as the shape control agent. In addition, it is preferable to use germanium compounds as the shape control agent, from the viewpoint of being able to produce plate-like alumina particles with a higher aspect ratio and a larger particle size than when silicon or silicon compounds are used. By the above-mentioned flux method using silicon or a silicon compound as the shape control agent, plate-like alumina particles containing mullite on the surface layer can be easily produced. By the above-mentioned flux method using a raw germanium compound as a shape control agent, plate-like alumina particles containing germanium or a germanium compound can be easily produced.
[0097] Silicon or silicon compounds Silicon or silicon compounds containing silicon element are not particularly limited, and known compounds can be used. Specific examples of silicon or silicon compounds containing silicon element include artificially synthesized silicon compounds such as metal silicon, organosilane, silicon resin, silica fine particles, silica gel, mesoporous silica, SiC, and mullite; and natural silicon compounds such as biosilica. Among these, organosilane, silicon resin, and silica fine particles are preferably used from the viewpoint of forming a more uniform composite or mixture with an aluminum compound. The silicon compounds containing silicon or silicon element may be used alone or in combination of two or more kinds. In addition, they may be used in combination with other shape control agents as long as the effect of the present invention is not impaired.
[0098] The shape of silicon or a silicon compound containing elemental silicon is not particularly limited, and for example, a sphere, an amorphous shape, an aspected structure (wire, fiber, ribbon, tube, etc.), a sheet, etc. can be suitably used.
[0099] Germanium compounds The raw germanium compound used as the shape control agent is not particularly limited, and known compounds can be used. Specific examples of the raw germanium compound include germanium metal, germanium dioxide, germanium monoxide, germanium tetrachloride, and organic germanium compounds having Ge-C bonds. The raw germanium compound may be used alone or in combination of two or more. In addition, it may be used in combination with other shape control agents as long as it does not impair the effects of the present invention.
[0100] The shape of the raw material germanium compound is not particularly limited, and for example, a sphere, an amorphous shape, an aspected structure (wire, fiber, ribbon, tube, etc.), a sheet, etc. can be suitably used.
[0101] (Molybdenum Compounds) The molybdenum compound contains elemental molybdenum and functions as a fluxing agent in the growth of α-crystals of alumina, as described below. The molybdenum compound is not particularly limited, but may be, for example, molybdenum oxide, an acid radical anion (MoO x n- ) is included.
[0102] The acid radical anion (MoO x n- ) is not particularly limited, but may be, for example, molybdic acid, sodium molybdate, potassium molybdate, lithium molybdate, HPMo 12 O 40 , H3SiMo 12 O 40 , NH4Mo7O 12 , molybdenum disulfide, etc.
[0103] The molybdenum compound may contain silicon, in which case the molybdenum compound containing silicon serves as both a flux agent and a shape control agent.
[0104] Among the above molybdenum compounds, it is preferable to use molybdenum oxide, which is easy to sublimate and is cost-effective. The above molybdenum compounds may be used alone or in combination of two or more kinds.
[0105] In addition, potassium molybdate (K2Mo n O 3n+1(n=1 to 3) contains potassium and therefore may also function as a potassium compound, which will be described later. In the manufacturing method of the embodiment, using potassium molybdate as a fluxing agent is synonymous with using a molybdenum compound and a potassium compound as fluxing agents.
[0106] (Potassium compounds) A potassium compound may be further used in combination with the shape control agent. The potassium compound is not particularly limited, but includes potassium chloride, potassium chlorite, potassium chlorate, potassium sulfate, potassium hydrogen sulfate, potassium sulfite, potassium hydrogen sulfite, potassium nitrate, potassium carbonate, potassium hydrogen carbonate, potassium acetate, potassium oxide, potassium bromide, potassium bromate, potassium hydroxide, potassium silicate, potassium phosphate, potassium hydrogen phosphate, potassium sulfide, potassium hydrogen sulfide, potassium molybdate, potassium tungstate, etc. In this case, the potassium compound includes isomers, as in the case of molybdenum compounds. Among these, it is preferable to use potassium carbonate, potassium hydrogen carbonate, potassium oxide, potassium hydroxide, potassium chloride, potassium sulfate, and potassium molybdate, and it is more preferable to use potassium carbonate, potassium hydrogen carbonate, potassium chloride, potassium sulfate, and potassium molybdate.
[0107] The above potassium compounds may be used alone or in combination of two or more kinds.
[0108] The potassium compound contributes to efficient formation of mullite on the alumina surface layer, and also contributes to efficient formation of a germanium-containing layer on the alumina surface layer.
[0109] It is also preferable to use a potassium compound together with a molybdenum compound as a fluxing agent.
[0110] Among the above, potassium molybdate contains molybdenum, and therefore can also function as the molybdenum compound described above. When potassium molybdate is used as a fluxing agent, it can exert the same effect as when a molybdenum compound and a potassium compound are used as fluxing agents.
[0111] As the potassium compound used when the raw materials are charged or generated in a reaction during the temperature rise process during calcination, a water-soluble potassium compound, for example, potassium molybdate, does not vaporize even in the calcination temperature range and can be easily recovered by washing after calcination. This reduces the amount of molybdenum compounds released outside the calcination furnace, and also enables a significant reduction in production costs.
[0112] When a molybdenum compound and a potassium compound are used as a fluxing agent, the molar ratio of the molybdenum element of the molybdenum compound to the potassium element of the potassium compound (molybdenum element / potassium element) is preferably 5 or less, more preferably 0.01 to 3, and even more preferably 0.5 to 1.5, since this can further reduce production costs. When the molar ratio (molybdenum element / potassium element) is within the above range, this is preferable because plate-like alumina particles having a large particle size can be obtained.
[0113] (metal compound) The metal compound can have a function of promoting the crystal growth of alumina, as described below. The metal compound can be used during firing as desired. Note that since the metal compound has a function of promoting the crystal growth of α-alumina, it is not essential for the production of the plate-like alumina particles according to the present invention.
[0114] The metal compound is not particularly limited, but preferably contains at least one selected from the group consisting of Group II metal compounds and Group III metal compounds.
[0115] Examples of the Group II metal compound include magnesium compounds, calcium compounds, strontium compounds, and barium compounds.
[0116] Examples of the Group III metal compound include a scandium compound, an yttrium compound, a lanthanum compound, and a cerium compound.
[0117] The above-mentioned metal compounds refer to oxides, hydroxides, carbonates, and chlorides of metal elements. For example, yttrium compounds include yttrium oxide (Y2O3), yttrium hydroxide, and yttrium carbonate. Of these, the metal compounds are preferably oxides of metal elements. These metal compounds include isomers.
[0118] Among these, the metal compounds of the third periodic elements, the metal compounds of the fourth periodic elements, the metal compounds of the fifth periodic elements, and the metal compounds of the sixth periodic elements are preferred, the metal compounds of the fourth periodic elements and the metal compounds of the fifth periodic elements are more preferred, and the metal compounds of the fifth periodic elements are even more preferred. Specifically, it is preferred to use magnesium compounds, calcium compounds, yttrium compounds, and lanthanum compounds, it is more preferred to use magnesium compounds, calcium compounds, and yttrium compounds, and it is particularly preferred to use yttrium compounds.
[0119] The addition rate of the metal compound is preferably 0.02 to 20 mass% based on the mass equivalent value of aluminum atoms in the aluminum compound, and more preferably 0.1 to 20 mass%. When the addition rate of the metal compound is 0.02 mass% or more, the crystal growth of α-alumina containing molybdenum can proceed favorably, which is preferable. On the other hand, when the addition rate of the metal compound is 20 mass% or less, it is preferable that plate-like alumina particles having a low content of impurities derived from the metal compound can be obtained.
[0120] [yttrium] When an aluminum compound is calcined in the presence of an yttrium compound as a metal compound, crystal growth proceeds more favorably in the calcination process, and α-alumina and a water-soluble yttrium compound are produced. At this time, the water-soluble yttrium compound is likely to be localized on the surface of the α-alumina, which is a plate-like alumina particle, so that if necessary, the yttrium compound can be removed from the plate-like alumina particle by washing with water, alkaline water, or a liquid obtained by heating these.
[0121] The amounts of the above aluminum compounds, molybdenum compounds, silicon or silicon compounds, germanium compounds, potassium compounds, etc. used are not particularly limited. For example, when the total amount of the raw materials calculated as oxides is taken as 100 mass %, the following mixture may be fired. 1) An aluminum compound having an aluminum content of preferably 50 mass% or more, more preferably 70 mass% or more and 99 mass% or less, and even more preferably 80 mass% or more and 94.5 mass% or less, calculated as Al2O3, A molybdenum compound that is preferably 40% by mass or less, more preferably 0.5% by mass or more and 20% by mass or less, and even more preferably 1% by mass or more and 7% by mass or less, calculated as MoO3, Silicon, a silicon compound, or a germanium compound, preferably 0.1% by mass or more and 10% by mass or less, in terms of SiO2 or GeO2, more preferably 0.5% by mass or more and less than 7% by mass of silicon, a silicon compound, or a germanium compound, and even more preferably 0.8% by mass or more and 4% by mass or less of silicon, a silicon compound, or a germanium compound, A mixed mixture.
[0122] From the viewpoint of obtaining plate-like alumina particles having a larger particle size, it is preferable to use in the above mixture, in terms of MoO3, preferably 7 mass % or more and 40 mass % or less of molybdenum compound, more preferably 9 mass % or more and 30 mass % or less of molybdenum compound, and further preferably 10 mass % or more and 17 mass % or less of molybdenum compound.
[0123] From the viewpoint of obtaining platelet alumina particles having a larger particle size, it is preferable to use in the above mixture silicon, silicon compounds and / or germanium compounds in an amount, calculated as SiO2 and / or GeO2, of preferably 0.4% by mass or more and less than 10% by mass, more preferably 0.5% by mass or more and 10% by mass or less, and particularly preferably 1% by mass or more and 3% by mass or less.
[0124] The silicon, silicon compound and / or germanium compound of the shape control agent may be silicon or a silicon compound, or may be a germanium compound. As the shape control agent, only silicon or a silicon compound may be used, only a germanium compound may be used, or only a combination of silicon or a silicon compound and a germanium compound may be used. When a germanium compound is used as the shape control agent, the mixture may contain preferably 0.4 mass % or more and less than 1.5 mass %, and more preferably 0.7 mass % or more and 1.2 mass % or less of the germanium compound, calculated as GeO2, when the total amount of the raw materials calculated as oxide is taken as 100 mass %.
[0125] The above raw material blending (mass%) conditions may be freely combined for each raw material, and the lower and upper limits in each raw material blending (mass%) may also be freely combined.
[0126] By using various compounds within the above ranges, it is possible to easily produce plate-like alumina particles that satisfy the above-mentioned longitudinal relaxation time T1 value and have excellent corrosion prevention effects.
[0127] When the mixture further contains the potassium compound, the amount of the potassium compound used is not particularly limited, but when the total amount of the raw materials calculated as oxide is taken as 100 mass%, the potassium compound can be mixed in an amount of preferably 5 mass% or less, more preferably 0.01 mass% or more and 3 mass% or less, and even more preferably 0.05 mass% or more and 1 mass% or less, calculated as KO. It is believed that the potassium molybdate formed by the reaction with the molybdenum compound using the potassium compound has an effect of diffusing silicon and contributes to the promotion of the formation of mullite on the surface of the plate-like alumina particles. Similarly, it is believed that the use of a potassium compound causes potassium molybdate formed by reaction with a molybdenum compound to have an effect on the diffusion of the starting germanium, and contribute to promoting the formation of germanium or germanium compounds on the surface of the platelet alumina particles. As the potassium compound used when the raw materials are charged or generated in a reaction during the temperature rise process during calcination, a water-soluble potassium compound, for example, potassium molybdate, does not vaporize even in the calcination temperature range and can be easily recovered by washing after calcination. This reduces the amount of molybdenum compounds released outside the calcination furnace, and also enables a significant reduction in production costs.
[0128] In the flux method, it is also preferable to use a molybdenum compound and a potassium compound as fluxing agents. The compound containing molybdenum and potassium as a fluxing agent can be produced, for example, in the firing process using a molybdenum compound and a potassium compound, which are cheaper and easier to obtain, as raw materials. Here, the case where a molybdenum compound and a potassium compound are used as fluxing agents will be described as an example, combining the case where a molybdenum compound and a potassium compound are used as fluxing agents and the case where a compound containing molybdenum and potassium is used as fluxing agents.
[0129] Furthermore, from the viewpoint of obtaining plate-like alumina particles with a larger particle size, the amounts of the above aluminum compound, molybdenum compound, potassium compound, and silicon or silicon compound used can be preferably as follows, when the total amount of the raw materials calculated as oxide is taken as 100 mass %. 2) A mixture of aluminum compounds of 10% by mass or more calculated as Al2O3, molybdenum compounds of 20% by mass or more calculated as MoO3, potassium compounds of 1% by mass or more calculated as K2O, and silicon or silicon compounds of less than 1% by mass calculated as SiO2. In terms of being able to further increase the content of high-quality hexagonal plate-shaped alumina, when the total amount of the raw materials calculated as oxide is taken as 100 mass %, it is more preferable to use the following mixture. 3) A mixture of an aluminum compound having an amount of 20% by mass or more and 70% by mass or less, calculated as Al2O3, a molybdenum compound having an amount of 30% by mass or more and 80% by mass or less, calculated as MoO3, a potassium compound having an amount of 5% by mass or more and 30% by mass or less, calculated as K2O, and a silicon or silicon compound having an amount of 0.001% by mass or more and 0.3% by mass or less, calculated as SiO2. In terms of being able to further increase the content of hexagonal plate-shaped alumina, it is more preferable to use the following mixtures when the total amount of the raw materials calculated as oxide is taken as 100 mass %. 4) A mixture of an aluminum compound having an amount of 25% by mass or more and 40% by mass or less, calculated as Al2O3, a molybdenum compound having an amount of 45% by mass or more and 70% by mass or less, calculated as MoO3, a potassium compound having an amount of 10% by mass or more and 20% by mass or less, calculated as K2O, and a silicon or silicon compound having an amount of 0.01% by mass or more and 0.1% by mass or less, calculated as SiO2. In order to maximize the content of hexagonal plate-shaped alumina and promote crystal growth more favorably, the following mixtures can be particularly preferably used. 5) A mixture of aluminum compounds of 35% by mass or more and 40% by mass or less when calculated as Al2O3, molybdenum compounds of 45% by mass or more and 65% by mass or less when calculated as MoO3, potassium compounds of 10% by mass or more and 20% by mass or less when calculated as K2O, and silicon or silicon compounds of 0.02% by mass or more and 0.08% by mass or less when calculated as SiO2, when the total amount of raw materials calculated as oxides is taken as 100% by mass.
[0130] By blending various compounds within the above range, plate-shaped alumina particles having a large particle size and excellent corrosion prevention effect can be produced. In particular, by increasing the amount of molybdenum used and decreasing the amount of silicon used to a certain extent, the particle size and crystallite diameter can be made larger, and hexagonal plate-shaped alumina particles can be easily obtained. By blending various compounds within the above more preferred range, hexagonal plate-shaped alumina particles can be easily obtained, the content of the hexagonal plate-shaped alumina particles can be further increased, and the corrosion prevention effect of the obtained alumina particles tends to be even better.
[0131] When the mixture further contains the above-mentioned yttrium compound, the amount of the yttrium compound is not particularly limited, but when the total amount of raw materials calculated as oxide is 100 mass%, preferably, the yttrium compound is mixed in an amount of 5 mass% or less, more preferably, 0.01 mass% or more and 3 mass% or less, calculated as Y2O3. In order to more suitably advance crystal growth, more preferably, when the total amount of raw materials calculated as oxide is 100 mass%, the yttrium compound is mixed in an amount of 0.1 mass% or more and 1 mass% or less, calculated as Y2O3.
[0132] The above-mentioned ranges of the amounts of the respective raw materials used can be appropriately combined as long as the total content does not exceed 100% by mass.
[0133] [Firing process] The calcination step is a step of calcining an aluminum compound in the presence of a molybdenum compound and a shape control agent, and may be a step of calcining the mixture obtained in the mixing step.
[0134] The plate-like alumina particles can be obtained, for example, by calcining an aluminum compound in the presence of a molybdenum compound and a shape control agent. As described above, this production method is called the flux method.
[0135] The flux method is classified as a solution method. More specifically, the flux method is a crystal growth method that utilizes the fact that the crystal-flux two-component phase diagram shows a eutectic type. The mechanism of the flux method is presumed to be as follows. That is, when a mixture of a solute and flux is heated, the solute and flux become liquid phase. At this time, since the flux is a flux, in other words, since the solute-flux two-component phase diagram shows a eutectic type, the solute melts at a temperature lower than its melting point and forms a liquid phase. If the flux is evaporated in this state, the concentration of the flux decreases, in other words, the effect of the flux in lowering the melting point of the solute is reduced, and the evaporation of the flux becomes the driving force to cause crystal growth of the solute (flux evaporation method). The solute and flux can also cause crystal growth of the solute by cooling the liquid phase (slow cooling method).
[0136] The flux method has the advantages of being able to grow crystals at temperatures much lower than the melting point, being able to precisely control the crystal structure, and being able to form idiomorphic crystals.
[0137] In the production of α-alumina particles by the flux method using a molybdenum compound as a flux, the mechanism is not necessarily clear, but it is presumed to be due to the following mechanism, for example. That is, when an aluminum compound is calcined in the presence of a molybdenum compound, aluminum molybdate is first formed. At this time, as can be understood from the above explanation, the aluminum molybdate grows α-alumina crystals at a temperature lower than the melting point of alumina. Then, for example, through the decomposition of aluminum molybdate and the evaporation of the flux, the crystal growth is accelerated, and alumina particles can be obtained. That is, the molybdenum compound functions as a flux, and α-alumina particles are produced via an intermediate called aluminum molybdate.
[0138] In the production of α-alumina particles by the flux method when a potassium compound is further used as a fluxing agent, the mechanism is not necessarily clear, but it is presumed to be due to the following mechanism, for example. First, a molybdenum compound reacts with an aluminum compound to form aluminum molybdate. Then, for example, aluminum molybdate decomposes to form molybdenum oxide and alumina, and at the same time, the molybdenum compound containing molybdenum oxide obtained by the decomposition reacts with a potassium compound to form potassium molybdate. The alumina crystals grow in the presence of the molybdenum compound containing potassium molybdate, and thus the plate-like alumina particles according to the embodiment can be obtained.
[0139] By the above-mentioned flux method, it is possible to produce plate-like alumina particles that satisfy the above-mentioned value of the longitudinal relaxation time T1 and have excellent corrosion prevention effect.
[0140] The calcination method is not particularly limited, and can be performed by a known and commonly used method. When the calcination temperature exceeds 700°C, the aluminum compound reacts with the molybdenum compound to form aluminum molybdate. When the calcination temperature exceeds 900°C, the aluminum molybdate decomposes and forms plate-like alumina particles due to the action of the shape control agent. In the plate-like alumina particles, the aluminum molybdate decomposes to form alumina and molybdenum oxide, and the molybdenum compound is considered to be incorporated into the aluminum oxide particles. Furthermore, when the firing temperature is 900° C. or higher, it is believed that a molybdenum compound (eg, molybdenum trioxide) obtained by decomposition of aluminum molybdate reacts with a potassium compound to form potassium molybdate. Furthermore, when the firing temperature reaches 1000°C or higher, in the presence of molybdenum, the crystals of the platelet alumina particles grow and the Al2O3 and SiO2 on the surfaces of the platelet alumina particles react with each other, forming mullite with high efficiency. Similarly, when the firing temperature reaches 1000°C or higher, in the presence of molybdenum, the Al2O3 on the surface of the platelet alumina particles reacts with the Ge compounds as the crystals of the platelet alumina particles grow, resulting in the efficient formation of germanium dioxide and compounds having Ge-O-Al.
[0141] In addition, the state of the aluminum compound, the shape control agent, and the molybdenum compound during firing is not particularly limited, and it is sufficient that the molybdenum compound and the shape control agent are present in the same space where they can act on the aluminum compound. Specifically, they may be simply mixed by mixing the powders of the molybdenum compound, the shape control agent, and the aluminum compound, mechanically mixed using a grinder, or mixed using a mortar, or may be mixed in a dry or wet state.
[0142] The firing temperature is not particularly limited, and is appropriately determined depending on the longitudinal relaxation time T1, (006 / 113) ratio, average particle size, aspect ratio, mullite formation, dispersibility, etc. of the target plate-like alumina particles. Usually, the firing temperature is preferably 900°C or higher, which is the decomposition temperature of aluminum molybdate (Al2(MoO4)3), more preferably 1000°C or higher at which mullite or germanium compounds are formed with high efficiency, and more preferably 1200°C or higher at which plate-like alumina particles with the longitudinal relaxation time T1 of 5 seconds or more (high crystallinity) can be easily obtained.
[0143] Generally, to control the shape of α-alumina obtained after firing, it is necessary to perform firing at high temperatures of over 2000°C, which is close to the melting point of α-alumina. However, there are significant challenges to be overcome in terms of the burden on the firing furnace and fuel costs in order to utilize this method industrially.
[0144] The manufacturing method of the embodiment can be carried out even at high temperatures exceeding 2000°C, but even at temperatures below 1600°C, which are significantly lower than the melting point of α-alumina, it is possible to form α-alumina that has a high α-crystallization rate and a high aspect ratio in a plate-like shape regardless of the shape of the precursor.
[0145] According to one embodiment of the present invention, even when the maximum firing temperature is 900 to 1600°C, plate-like alumina particles having a high aspect ratio and an α-crystallization rate of 90% or more can be formed efficiently at low cost. It is more preferable to fire at a maximum temperature of 950 to 1500°C, even more preferable to fire at a maximum temperature in the range of 1000 to 1400°C, and most preferable to fire at a maximum temperature of 1200 to 1400°C.
[0146] Regarding the firing time, it is preferable that the time required to raise the temperature to the predetermined maximum temperature is within the range of 15 minutes to 10 hours, and that the holding time at the firing maximum temperature is within the range of 5 minutes to 30 hours. In order to efficiently form plate-like alumina particles, it is more preferable that the firing holding time is about 10 minutes to 15 hours. By selecting conditions of a maximum temperature of 1000 to 1400°C and a firing holding time of 10 minutes to 15 hours, dense α-crystal polygonal plate-like alumina particles are easily obtained without aggregation. By selecting conditions of a maximum temperature of 1200 to 1400° C. and a firing holding time of 10 minutes to 15 hours, plate-like alumina particles having the longitudinal relaxation time T1 of 5 seconds or more (high crystallinity) can be easily obtained.
[0147] The firing atmosphere is not particularly limited as long as the effects of the present invention can be obtained. For example, an oxygen-containing atmosphere such as air or oxygen, or an inert atmosphere such as nitrogen, argon, or carbon dioxide is preferable, and an air atmosphere is more preferable in terms of cost.
[0148] The calcination apparatus is not necessarily limited, and a so-called calcination furnace can be used. The calcination furnace is preferably made of a material that does not react with the sublimated molybdenum oxide, and it is preferable to use a highly airtight calcination furnace so as to efficiently utilize the molybdenum oxide.
[0149] The alumina particles are preferably obtained by calcining an aluminum compound in the presence of a molybdenum compound and a shape-controlling agent, or in the presence of a molybdenum compound, a shape-controlling agent, a potassium compound and a metal oxide.
[0150] That is, a preferred method for producing alumina particles includes a step of calcining an aluminum compound in the presence of a molybdenum compound and a shape control agent, or in the presence of a molybdenum compound, a shape control agent and a potassium compound (calcination step). The mixture preferably further contains the above-mentioned metal compound. The metal compound is preferably a yttrium compound.
[0151] [Cooling process] When a molybdenum compound and a potassium compound are used as fluxing agents, the method for producing alumina particles may include a cooling step. The cooling step is a step of cooling the alumina crystal-grown in the firing step. More specifically, the cooling step may be a step of cooling a composition containing the alumina obtained by the firing step and the fluxing agent in a liquid phase.
[0152] The cooling rate is not particularly limited, but is preferably 1 to 1000°C / hour, more preferably 5 to 500°C / hour, and even more preferably 50 to 100°C / hour. A cooling rate of 1°C / hour or more is preferable because the manufacturing time can be shortened. On the other hand, a cooling rate of 1000°C / hour or less is preferable because the firing container is less likely to crack due to heat shock and can be used for a long time.
[0153] The cooling method is not particularly limited, and may be natural cooling or a cooling device may be used.
[0154] [Post-processing process] The method for producing plate-like alumina particles according to the embodiment may include a post-treatment step. The post-treatment step is a post-treatment step for the plate-like alumina particles, and is a step for removing a fluxing agent. The post-treatment step may be performed after the above-mentioned firing step, after the above-mentioned cooling step, or after the firing step and the cooling step. In addition, the post-treatment step may be repeated two or more times as necessary.
[0155] Post-treatment methods include washing and high temperature treatment, which may be performed in combination.
[0156] The washing method is not particularly limited, but the metal oxide can be removed by washing with water, an aqueous ammonia solution, an aqueous sodium hydroxide solution, or an acidic aqueous solution.
[0157] In this case, the molybdenum content can be controlled by appropriately changing the concentrations and amounts of water, ammonia aqueous solution, sodium hydroxide aqueous solution, and acidic aqueous solution used, as well as the cleaning locations and cleaning times.
[0158] As a method of high temperature treatment, a method of raising the temperature to the sublimation point or boiling point of the flux or higher can be mentioned.
[0159] [Crushing process] In the fired product, the plate-like alumina particles may aggregate and not satisfy the preferred particle size range, so the plate-like alumina particles may be pulverized as necessary to satisfy the preferred particle size range. The method for pulverizing the fired product is not particularly limited, and any conventionally known pulverizing method such as a ball mill, a jaw crusher, a jet mill, a disk mill, a spectromill, a grinder, or a mixer mill can be used.
[0160] [Classification process] The plate-like alumina particles are preferably classified to adjust the average particle size, improve the powder flowability, or suppress the increase in viscosity when mixed with a binder to form a matrix. "Classification" refers to an operation of classifying particles into groups based on their size. The classification may be either wet or dry, but from the viewpoint of productivity, dry classification is preferred. Dry classification includes classification by sieving, as well as wind classification, which classifies based on the difference between centrifugal force and fluid drag, but from the viewpoint of classification accuracy, wind classification is preferred, and can be performed using a classifier such as an air classifier utilizing the Coanda effect, a swirling air classifier, a forced vortex centrifugal classifier, or a semi-free vortex centrifugal classifier. The above-mentioned pulverization step and classification step can be carried out at any stage required, including before or after the organic compound layer forming step described later. Depending on whether or not the pulverization or classification is carried out and the selection of the conditions therefor, for example, the average particle size of the obtained plate-like alumina particles can be adjusted.
[0161] The plate-like alumina particles of the embodiment or the plate-like alumina particles obtained by the manufacturing method of the embodiment are preferably those with little or no aggregation, because they easily exhibit their inherent properties, are more easily handled, and have better dispersibility when dispersed in a dispersion medium. In the manufacturing method of the plate-like alumina particles, if the above-mentioned pulverization step or classification step is not performed and the plate-like alumina particles with little or no aggregation are obtained, there is no need to perform the steps, and the plate-like alumina having the desired excellent properties can be manufactured with high productivity, which is preferable.
[0162] [Organic compound layer formation process] In one embodiment, the method for producing plate-like alumina particles may further include an organic compound layer forming step, which is usually performed after the firing step or after the post-treatment step.
[0163] The method for forming the organic compound layer is not particularly limited, and any known method can be appropriately adopted. For example, a method in which a liquid containing an organic compound is brought into contact with plate-like alumina particles containing molybdenum, and then dried can be mentioned.
[0164] As the organic compound that can be used to form the organic compound layer, for example, the above-mentioned compounds can be used.
[0165] <Corrosion-resistant paint> The corrosion inhibitor of the present embodiment is preferably blended in the corrosion inhibitor. As one embodiment of the present invention, an anticorrosive paint containing the corrosion inhibitor of the embodiment (hereinafter, sometimes referred to as "anticorrosive paint of the embodiment" or simply "anticorrosive paint") can be provided. The anticorrosive paint is preferably used as an anticorrosive paint for steel structures such as vehicles, bridges, and plant facilities, an iron rust prevention paint, and particularly as an iron rust prevention paint for undercoat.
[0166] The anticorrosive coating material of this embodiment may contain various optional components, if necessary, in addition to the plate-like alumina particles, such as solvents, resins, drying accelerators, hardeners, hardening accelerators, thickeners, anti-settling agents, anti-cracking agents, anti-sagging agents, flow-extending agents, anti-foaming agents, UV absorbers, light stabilizers, and other pigments that do not fall under the category of the plate-like alumina particles.
[0167] As one embodiment of the present invention, there can be provided an anticorrosive coating material containing the platelet alumina particles of the embodiment, a solvent, and a resin. As one embodiment of the present invention, there can be provided an anticorrosive coating material containing the platelet alumina particles of the embodiment, a solvent, a resin, and a drying accelerator.
[0168] From the viewpoint of reducing the viscosity of the anticorrosive coating material and facilitating application, it is preferable that the anticorrosive coating material contains a solvent. The solvent is capable of dispersing the plate-like alumina particles. The solvent is capable of dispersing or dissolving the optional components. Examples of the solvent include alcohol-based solvents such as ethyl alcohol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, and isobutyl alcohol; ester-based solvents such as ethyl acetate, propyl acetate, and butyl acetate, and ketone-based solvents such as methyl ethyl ketone, methyl butyl ketone, and cyclohexanone; ether ester-based solvents such as methyl cellosolve acetate and butyl cellosolve acetate; amide-based solvents such as dimethylformamide and dimethylacetamide; aromatic hydrocarbon-based solvents such as toluene and xylene; aliphatic hydrocarbon-based solvents such as hexane, heptane, and white spirits; mixed solvents of aromatic hydrocarbons and aliphatic hydrocarbons such as mineral spirits; water, mixtures thereof, and the like, but are not limited to these.
[0169] The content of the solvent relative to the total mass (100 mass %) of the anticorrosive coating may be, for example, 3 to 90 mass %, or may be 5 to 85 mass %.
[0170] The content of solids (components excluding volatile components such as solvents) relative to the total mass (100% by mass) of the anticorrosive coating may be, for example, 10 to 97% by mass, or 15 to 95% by mass.
[0171] From the viewpoint of binding the plate-like alumina particles contained in the anticorrosive coating material together and increasing the adhesion between the substrate and the anticorrosive coating material, it is preferable that the anticorrosive coating material contains a resin. As the resin, any resin that can be blended in paint can be used, and a conventionally known resin may be used. Examples of the resin include acrylic resin, polyester resin, alkyd resin, urethane resin, epoxy resin, vinyl chloride-vinyl acetate copolymer resin, polyamide resin, melamine resin, etc. One type of resin may be used alone, or two or more types may be used in combination. The content of the resin (solid content) in the anticorrosive paint may be 5 mass% or more, 10 to 97 mass%, or 30 to 80 mass% relative to 100 mass% of the total mass of the solid content of the anticorrosive paint (components excluding volatile components such as solvents).
[0172] From the viewpoint of effectively exerting the anti-corrosion effect, the content of the plate-like alumina particles in the anti-corrosion paint may be 3 mass% or more, 3 to 95 mass%, 10 to 70 mass%, or 20 to 60 mass%, relative to 100 mass% of the total mass of the solids content of the anti-corrosion paint (components excluding volatile components such as solvents).
[0173] Pigment volume concentration (PVC) represents the ratio of the binder component to the pigment, and is a value expressed as pigment volume / pigment volume+binder component volume. The critical pigment volume concentration (CPVC) is the point at which all the voids between the pigment particles are filled with binder components. The binder component includes the above-mentioned resins.
[0174] From the viewpoint of effectively exerting the anti-corrosion effect and appropriately improving the strength of the coating film, the content of the platelet alumina particles in the anti-corrosion coating material may be, for example, 30 to 90 mass%, or 50 to 80 mass%, relative to 100 mass% of the alumina particle content at the critical pigment volume concentration (CPVC) when the platelet alumina particles are used as a pigment.
[0175] Similarly, from the viewpoint of effectively exerting the anticorrosive effect and appropriately improving the strength of the coating film, the mass ratio of p / b (pigment / binder component) may be, for example, 0.1 to 10, 0.5 to 2, or 0.7 to 1.5.
[0176] The drying accelerator may be, for example, a cobalt desiccant, such as cobalt naphthenate, cobalt octenate, or cobalt stearate.
[0177] Examples of other pigments that do not fall under the category of the above-mentioned plate-like alumina particles include various pigments such as color pigments and extender pigments. As the coloring pigment, conventionally known pigments can be appropriately used depending on the desired hue and performance. Examples of the coloring pigment include organic pigments such as azo pigments, benzimidazolone pigments, isoindolinone / isoindoline pigments, phthalocyanine pigments, quinacridone pigments, dioxazine pigments, diketopyrrolopyrrole pigments, quinophthalone pigments, perylene / perinone pigments, thioindigo pigments, anthraquinone pigments, and threne pigments, and inorganic pigments such as iron oxide, carbon black, titanium oxide, and zinc sulfide. Examples of the extender pigments include barium sulfate, calcium carbonate, talc, and kaolin. Furthermore, various metals such as zinc powder and aluminum powder or metal salts that can be used as anticorrosive pigments may be used in combination.
[0178] The anticorrosive coating material of the present embodiment can be produced, for example, by a method including mixing the plate-like alumina particles and, if necessary, the optional components described above. Examples of mixers that can be used in this process include a sand mill, a homomixer, a homogenizer, a colloid mill, a microfluidizer, a sonolator, and a cavitron.
[0179] <Laminate> The substrate coated with the anticorrosive coating of the embodiment can be provided as a laminate having the substrate and a layer containing the anticorrosive coating of the embodiment. Such a laminate is useful in that anticorrosive properties are imparted to the substrate. An example of the layer containing the anticorrosive coating is a cured product of the anticorrosive coating of the embodiment. The cured product of the anticorrosive coating can be formed, for example, by drying at room temperature or curing by heating the coating of the anticorrosive coating applied to the substrate.
[0180] The dry thickness of the layer containing the anticorrosive coating material is, for example, preferably 50 to 700 μm, more preferably 60 to 300 μm. When the dry thickness is within the above range, the anticorrosive effect is exhibited well.
[0181] The substrate is not particularly limited, but preferably includes a metal or a metal-containing material, and more specifically includes the above-mentioned steel structures such as vehicles, bridges, and plant facilities, or parts thereof.
[0182] <Method> The anticorrosive coating material of the present embodiment can be used by applying it to a substrate. That is, in one embodiment, the present invention provides a method for producing a laminate, which includes applying the anticorrosive coating material to a substrate. According to the method for producing a laminate of the present embodiment, the laminate having anticorrosive properties can be produced. The method of applying the anticorrosive coating is not particularly limited, and can be roll coating, spray, brush, spatula, bar coater, or dip coating. As a post-treatment method after coating, drying at room temperature to heat curing can be performed. When heat curing is performed, the heating temperature is preferably in the range of 50 to 250°C, and more preferably in the range of 60 to 230°C. The heating time is preferably in the range of 2 to 30 minutes, and more preferably in the range of 5 to 20 minutes.
[0183] As described above, the anticorrosive coating material of the present embodiment contains platelet alumina particles, which improves the chemical stability and strength of the coating film, and the anticorrosive coating material has excellent anticorrosive effect. In addition, since the anti-corrosion paint of this embodiment contains platelet alumina particles, the platelet alumina dispersed in the coating film is expected to prevent the diffusion of corrosive components into the metal, thereby suppressing corrosion of metals such as iron. Furthermore, when the anticorrosive paint contains the above-mentioned resin, the resin provides a barrier effect to prevent corrosion. Furthermore, by containing mullite in the surface layer of the plate-like alumina particles, adhesion to resin is improved, and further excellent corrosion prevention effect can be achieved. EXAMPLES
[0184] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples.
[0185] <Synthesis of plate-shaped alumina particles> [Synthesis Example 1] Synthesis of plate-shaped alumina particles 145.2 g of aluminum hydroxide (manufactured by Nippon Light Metals Co., Ltd., average particle size 2 μm), 0.90 g of silicon dioxide (manufactured by Kanto Chemical Co., Ltd., special grade), and 4.7 g of molybdenum trioxide (manufactured by Taiyo Koko Co., Ltd.) were mixed in a mortar to obtain a mixture. The obtained mixture was placed in a crucible, heated to 1200°C at 5°C / min in a ceramic electric furnace, and held at 1200°C for 10 hours for firing. After that, the temperature was lowered to room temperature at 5°C / min, and the crucible was removed to obtain 98.0 g of a light blue powder. The obtained powder was crushed in a mortar until it passed through a 106 μm sieve. Next, 98.0 g of the obtained light blue powder was dispersed in 150 mL of 0.5% ammonia water, and the dispersion solution was stirred at room temperature (25 to 30 ° C.) for 0.5 hours, after which the ammonia water was removed by filtration, and the molybdenum remaining on the particle surface was removed by washing with water and drying, to obtain 95.0 g of light blue powder. The obtained powder was confirmed to have a polygonal plate shape by SEM observation, with very few aggregates, and to be a plate-shaped particle with excellent handleability. Furthermore, when XRD measurement was performed, a sharp peak scattering due to α-alumina appeared, and no alumina crystal peak other than the α crystal structure was observed, confirming that it was a plate-shaped alumina with a dense crystal structure. In addition, the α conversion rate was 99% or more (almost 100%). Furthermore, from the results of fluorescent X-ray quantitative analysis, it was confirmed that the obtained particles contained 0.2 mass% molybdenum in terms of molybdenum trioxide and 0.70 mass% silicon in terms of silicon dioxide. The molar ratio of Si to Al [Si] / [Al] obtained from the XPS analysis was 0.23. The molar ratio of Si to Al [Si] / [Al] obtained from the XRF analysis was 0.007. The longitudinal relaxation time T1 for the 6-coordinate aluminum peak was 9 seconds.
[0186] [Synthesis Example 2] Synthesis of plate-shaped alumina particles 138.6 g of aluminum hydroxide (manufactured by Nippon Light Metals Co., Ltd., average particle size 2 μm), 0.9 g of silicon dioxide (manufactured by Kanto Chemical Co., Ltd., special grade), and 9.0 g of molybdenum trioxide (manufactured by Taiyo Koko Co., Ltd.) were mixed in a mortar to obtain a mixture. The obtained mixture was placed in a crucible, heated to 1200°C at 5°C / min in a ceramic electric furnace, and held at 1200°C for 10 hours for firing. After that, the temperature was lowered to room temperature at 5°C / min, and the crucible was removed to obtain 93.0 g of a light blue powder. The obtained powder was crushed in a mortar until it passed through a 106 μm sieve. Next, 93.0 g of the obtained light blue powder was dispersed in 150 mL of 0.5% ammonia water, and the dispersion solution was stirred at room temperature (25 to 30 ° C.) for 0.5 hours, after which the ammonia water was removed by filtration, and the molybdenum remaining on the particle surface was removed by washing with water and drying, to obtain 90.0 g of light blue powder. The obtained powder was confirmed to have a polygonal plate shape by SEM observation, with very few aggregates, and to be a plate-shaped particle with excellent handleability. Furthermore, when XRD measurement was performed, a sharp peak scattering due to α-alumina appeared, and no alumina crystal peak other than the α crystal structure was observed, confirming that it was a plate-shaped alumina with a dense crystal structure. In addition, the α conversion rate was 90% or more. Furthermore, from the results of fluorescent X-ray quantitative analysis, it was confirmed that the obtained particles contained 0.3 mass% molybdenum in terms of molybdenum trioxide and 0.70 mass% silicon in terms of silicon dioxide. The molar ratio of Si to Al [Si] / [Al] obtained from the XPS analysis was 0.27. The molar ratio of Si to Al [Si] / [Al] obtained from the XRF analysis was 0.007. The longitudinal relaxation time T1 for the 6-coordinate aluminum peak was 11.0 seconds.
[0187] [Synthesis Example 3] Synthesis of plate-like alumina particles 7.0 g of aluminum sulfate (Kanto Chemical Co., Ltd., Al2(SO4)3, 14-18 water of crystallization) and 10 g of potassium sulfate (Kanto Chemical Co., Ltd., K2SO4) were mixed uniformly to obtain a mixture. The mixture obtained was placed in a crucible, heated to 950-1100°C at 5°C / min in a ceramic electric furnace, and held at 950-1100°C for 5 hours to perform firing. After that, the temperature was lowered to room temperature at 5°C / min, and the crucible was removed to obtain 11.5 g of white powder. The obtained white powder was then washed with water and dried to obtain plate-like alumina.
[0188] <Evaluation of plate-like alumina particles obtained in synthesis examples> [Measurement of particle size L] The plate-like alumina particles obtained in the synthesis example were used as samples, and the median diameter D 50 (μm) was determined and regarded as the particle size L.
[0189] [Measurement of thickness D] The thickness of 50 samples thus produced was measured using a scanning electron microscope (SEM), and the average value was used as the thickness D (μm).
[0190] [Aspect ratio L / D] The aspect ratio of the plate-like alumina particles was calculated using the following formula.
[0191] Aspect ratio = average particle size L of plate-shaped alumina particles / thickness D of plate-shaped alumina particles
[0192] [Measurement of specific surface area] The prepared samples were pretreated at 300° C. for 3 hours, and the specific surface area of the pretreated samples was measured using a TriStar 3000 manufactured by Micromeritics.
[0193] [XRD peak intensity ratio - analysis of the presence or absence of mullite] The prepared sample was placed on a measurement sample holder with a depth of 0.5 mm and filled flat with a constant load. It was then set in a wide-angle X-ray diffraction (XRD) device (Ultima IV, Rigaku Corporation) and measurements were performed under the following conditions: Cu / Kα radiation, 40 kV / 40 mA, scan speed of 2 degrees / min, and scan range of 10 to 70 degrees. The peak height of mullite observed at 2θ = 26.2 ± 0.2 degrees was designated as A, the peak height of the (104) α-alumina plane observed at 2θ = 35.1 ± 0.2 degrees was designated as B, and the baseline value at 2θ = 30 ± 0.2 degrees was designated as C. The presence or absence of mullite was determined using the following formula. A value of 0.02 or more was judged to be "present" in mullite, and a value of less than 0.02 was judged to be "absent" in mullite.
[0194]
number
[0195] [Analysis of Alpha Conversion Rate] The prepared sample was placed on a measurement sample holder with a depth of 0.5 mm, and packed flat with a constant load. It was then set in a wide-angle X-ray diffractometer (Ultima IV, Rigaku Corporation) and measurements were performed under the conditions of Cu / Kα radiation, 40 kV / 40 mA, scan speed of 2 degrees / min, and a scan range of 10 to 70 degrees. The α conversion rate was calculated from the ratio of the strongest peak heights of α-alumina and transition alumina.
[0196] [Si content in the surface layer of plate-shaped alumina particles] Using an X-ray photoelectron spectroscopy (XPS) device, Quantera SXM (ULVAC-PHI, Inc.), the prepared sample was press-fixed onto double-sided tape and subjected to composition analysis under the following conditions.
[0197] (Measurement conditions) X-ray source: Monochromatic AlKα, beam diameter 100μmφ, output 25W Measurement: Area measurement (1000μm square), n=3 Charge correction: C1s=284.8eV
[0198] The [Si] / [Al] ratio determined from the results of XPS analysis was taken as the amount of Si in the surface layer of the plate-like alumina particles.
[0199] [Analysis of the amount of Si contained in plate-shaped alumina particles] Using an X-ray fluorescence (XRF) analyzer Primus IV (Rigaku Corporation), approximately 70 mg of the prepared sample was placed on filter paper, covered with PP film, and subjected to composition analysis. The [Si] / [Al] ratio obtained from the XRF analysis was taken as the amount of Si in the platelet alumina particles. The amount of silicon determined from the results of XRF analysis was calculated in terms of silicon dioxide (mass %) relative to 100 mass % of the plate-like alumina particles.
[0200] [Analysis of Mo content in plate-shaped alumina] Using a Primus IV X-ray fluorescence analyzer (Rigaku Corporation), approximately 70 mg of the prepared sample was placed on filter paper, covered with PP film, and subjected to composition analysis. The amount of molybdenum determined from the results of XRF analysis was calculated in terms of molybdenum trioxide (mass %) relative to 100 mass % of the plate-like alumina particles.
[0201] [Measurement of coordination number by NMR] Using JEOL RESONANCE's JNM-ECA600, a static magnetic field strength of 14.1T was applied to the solid 27 Al NMR analysis was performed. Each sample was collected in a φ4 mm solid-state NMR sample tube and measurements were performed. After measuring the 90-degree pulse width for each sample, relaxation time measurements by the saturation recovery method and single pulse measurements were performed.
[0202] The peak top of hexacoordinated aluminum in the commercially available reagent γ-alumina (Kanto Chemical) was assumed to be 14.6 ppm, and the peaks detected between 10 and 30 ppm were estimated to be hexacoordinated aluminum peaks, and the peaks detected between 60 and 90 ppm were estimated to be tetracoordinated aluminum peaks.
[0203] The conditions are as follows: -MAS rate:15kHz Probe: SH60T4 (JEOL RESONANCE)
[0204] The measurement conditions for single pulse measurement at 14.1T are as follows. Pulse delay time (seconds): (T1 (seconds) calculated by relaxation recovery method x 3) Pulse width (μsec): 90-degree pulse width of hexacoordinate aluminum of each sample (μsec) / 3 Number of times: 8 ·Temperature: 46℃
[0205] [Measurement of longitudinal relaxation time T1 by NMR] The longitudinal relaxation times T1 for the hexacoordinated aluminum peaks detected at 10-30 ppm were determined by the relaxation recovery method at 14.1 T.
[0206] The conditions are as follows: Pulse delay time (sec): 0.5 Post-saturation wait time (sec): 0.5-100, Exponential interval 16 points Number of times: 1 ·Temperature: 46℃
[0207] The composition of the raw material compounds calculated as oxides (total is 100 mass%) and the above evaluation results are shown in Table 1. In Table 1, "ND" is an abbreviation for "not detected," which indicates that the content was not detected.
[0208] [Table 1]
[0209] <Preparation of anti-corrosion paint> [Examples 1-2, Comparative Examples 1-2] The alumina pigment shown in Table 2 was added to a modified alkyd resin (product name "Beckosol (registered trademark) 11-035", solid content 50 mass%) so that the CPVC (critical pigment volume concentration) was 75%. Next, a cobalt drier was added in an amount of 2 mass% of the paint before dilution described below, and then the paint was diluted with xylene to a concentration suitable for spraying to obtain an anticorrosion paint.
[0210] <Evaluation of rust prevention> The corrosion-resistant coatings of Examples 1 and 2 and Comparative Examples 1 and 2 were evaluated for rust prevention as follows. A cold-rolled steel plate was prepared as a test panel. The test panel was washed with acetone and then left to stand for 1 hour. Prior to application of the corrosion-resistant coating, the back surface of the test panel was coated with a clear coat of automotive grade (trade name "2K Topcaots"). Each of the corrosion-resistant coatings of Examples 1 and 2 and Comparative Examples 1 and 2 was then spray-coated onto the test panel to form a dry film having a film thickness of 0.1524 mm. The film was cured at room temperature for 72 hours.
[0211] A water bath containing deionized water containing 0.5% sodium chloride was prepared and kept at 30°C. A part of the panel sprayed with the above anticorrosive paint was submerged in the water bath for 9 days and observed. Photographs of the panel were taken on each of the 1st to 9th days (except for the 4th and 5th days).
[0212] The evaluation results are shown in Table 2. ○: No rust was found on the test panel ×: Rust was observed on 50% or more of the immersed area of the test panel.
[0213] [Table 2]
[0214] From Table 2, it was confirmed that the anticorrosive paints of Examples 1 and 2 had better rust prevention properties than the anticorrosive paints of Comparative Examples 1 and 2.
[0215] The configurations and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of the configurations are possible without departing from the spirit of the present invention. Furthermore, the present invention is not limited to each embodiment, but is limited only by the scope of the claims. [Industrial Applicability]
[0216] According to the corrosion inhibitor of the present embodiment, it is possible to provide an inhibitor having a good corrosion prevention effect.
Claims
1. solid 27 In the Al NMR analysis, the longitudinal relaxation time T 1 The corrosion inhibitor contains plate-like alumina particles and has a surface layer containing mullite, and the surface layer has a resistance to corrosion of 9 seconds or more.
2. The corrosion inhibitor of claim 1 , wherein the platelet alumina particles contain molybdenum.
3. 3. The corrosion inhibitor according to claim 2, wherein the content of molybdenum relative to 100 mass% of the plate-like alumina particles is 0.1 to 1 mass% in terms of molybdenum trioxide.
4. An anticorrosive paint comprising the anticorrosive agent according to any one of claims 1 to 3.
5. A laminate comprising a substrate and a layer containing the anticorrosive coating according to claim 4.
6. The laminate of claim 5 , wherein the substrate is a metal.
7. A method for producing a laminate, comprising applying the anticorrosive coating according to claim 4 to a substrate.
8. A method for protecting a substrate from corrosion, comprising applying the anticorrosive coating composition according to claim 4 to the substrate.
Citation Information
Patent Citations
Method for synthesizing aluminum oxide powder
CN102107898A
Heavy corrosion-resistant composition
JP1989170670A
Anticorrosive coating composition
JP1994329959A
Plate-like boehmite, plate-like alumina, and method for producing them
JP2003002641A
Method of quantifying kaolins in coal
JP2004317423A
